How movies move us – movie preferences are linked to differences in neuronal emotion processing of fear and anger: an fMRI study - Zwiky, Esther; König, Philine; Herrmann, Rebekka Maria; Küttner, Antonia; Selle, Janine; Ptasczynski, Lena Esther; Schöniger, Konrad; Rutenkröger, Mareike; Enneking, Verena; Borgers, Tiana; Klug, Melissa; Dohm, Katharina; et al. (Frontiers in Behavioral Neuroscience, 2024)
As a source of audio-visual stimulation, movies expose people to various emotions. Interestingly, several genres are characterized by negative emotional content. Albeit theoretical approaches exist, little is known about preferences for specific movie genres and the neuronal processing of negative emotions. We investigated associations between movie genre preference and limbic and reward-related brain reactivity to close this gap by employing an fMRI paradigm with negative emotional faces in 257 healthy participants. We compared the functional activity of the amygdala and the nucleus accumbens (NAcc) between individuals with a preference for a particular movie genre and those without such preference. Amygdala activation was relatively higher in individuals with action movie preference (pTFCE-FWE = .013). Comedy genre preference was associated with increased amygdala (pTFCE-FWE = .038) and NAcc activity (pTFCE-FWE = .011). In contrast, crime/thriller preference (amygdala: pTFCE-FWE ≤ .010, NAcc: pTFCE-FWE = .036), as well as documentary preference, was linked to the decreased amygdala (pTFCE-FWE = .012) and NAcc activity (pTFCE-FWE = .015). The study revealed associations between participants' genre preferences and brain reactivity to negative affective stimuli. Interestingly, preferences for genres with similar emotion profiles (action, crime/thriller) were associated with oppositely directed neural activity. Potential links between brain reactivity and susceptibility to different movie-related gratifications are discussed.